Studi efektifitas penggunaan dinding geser pada bangunan hotel 15 lantai di Magelang, Jawa Tengah - Faraz Haiatul Maknun; Yosafat Aji Pranata (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
Earthquake-resistant buildings are structures designed to withstand lateral loads caused by earthquakes without damaging their structural elements. One effort that can be made is to use shear walls in medium-rise buildings. The purpose of this study is to study the behavior of the Aloon-Aloon Hotel multi-storey building located in Magelang City, which has medium soil characteristics with SDS of 0.61g and SD1 of 0.45g, risk category II. The scope of the study is a comparative study of buildings modeled with and without shear walls. Earthquake load planning refers to SNI 1726:2019 with the equivalent static analysis method. The process of modeling the building structure in this study uses three-dimensional structural analysis software based on the finite element method to study the behavior of the structure due to gravity loads and lateral loads. The results of the study are that buildings with shear walls have a higher building structure volume of 7.74% (shear walls, columns, beams) than buildings without shear walls (columns and beams). However, the use of shear walls produces lower deviation and capital values compared to buildings without shear walls, so that the building has high lateral stiffness in resisting lateral loads (designed earthquake loads). This shows that the use of shear walls significantly improves the strength and stiffness performance of structures in medium-rise buildings.